Gonioscopy-assisted Transluminal Trabeculotomy (GATT) is An Effective Procedure for Steroid-induced Glaucoma. Issue 9 (September 2019) - Boese, Erin A.; Shah, Manjool
Abstract : Precis: Gonioscopy-assisted transluminal trabeculotomy (GATT) is a novel technique that lowers intraocular pressure (IOP) by fracturing the trabecular meshwork. In this retrospective chart review, GATT was found to be effective at lowering the intraocular pressure for steroid-induced glaucoma (SIG). Purpose: GATT is a novel microinvasive glaucoma surgery that builds on traditional trabeculotomy techniques to decrease the proximal resistance of conventional outflow, and it is proposed to be an effective surgical treatment for SIG. The purpose of this study is to evaluate the efficacy of GATT for lowering the IOP in SIG. Methods and Patients: A retrospective chart review was performed of all GATT procedures performed on patients with a predominant diagnosis of steroid-induced glaucoma between March 1, 2016 and March 30, 2018 at the University of Michigan. Primary outcome measures include IOP, the number of IOP-lowering medications prescribed, and the topical steroid dosing over the duration of follow-up. Results: A total of 13 patients with steroid-induced glaucoma underwent the GATT procedure. There was a significant reduction in the mean IOP at all postoperative visits. The average IOP decreased by 16.4 (55%) to 19.5 mm Hg (63%) between 3 and 24 months postoperatively. By 24 months, all patients had a reduction in IOP of >20%. The number of glaucoma medications also decreased significantly from an average of 3.1 medications preoperatively to an average of 0.8 medications at last follow-up. The majority of patients (>67%) required continued use of steroids at all postoperative visits. The most common postoperative complication was a transient hyphema (38%). No patients required a repeat glaucoma surgery or anterior chamber washout. Conclusions: This small case series suggests that GATT is an effective and safe surgical technique to decrease IOP and decrease medication burden in patients with predominantly steroid-induced glaucoma. To our knowledge, this is the first study looking specifically at the efficacy of GATT for predominantly SIG. Abstract : Supplemental Digital Content is available in the text.